Identification of genetic susceptibility for Chinese migraine with depression using machine learning - An, Xingkai; Zhao, Shanshan; Fang, Jie; Li, Qingfang; Yue, Cen; Jing, Chuya; Zhang, Yidan; Zhang, Jiawei; Zhou, Jie; Chen, Caihong; Qu, Hongli; Ma, Qilin; et al. (Frontiers in Neurology, 2024)
Background Migraine is a common primary headache that has a significant impact on patients’ quality of life. The co-occurrence of migraine and depression is frequent, resulting in more complex symptoms and a poorer prognosis. The evidence suggests that depression and migraine comorbidity share a polygenic genetic background. Objective The aim of this study is to identify related genetic variants that contribute to genetic susceptibility to migraine with and without depression in a Chinese cohort. Methods In this case-control study, 263 individuals with migraines and 223 race-matched controls were included. Eight genetic polymorphism loci selected from the GWAS were genotyped using Sequenom’s MALDI-TOF iPLEX platform. Results In univariate analysis, ANKDD1B rs904743 showed significant differences in genotype and allele distribution between migraineurs and controls. Furthermore, a machine learning approach was used to perform multivariate analysis. The results of the Random Forest algorithm indicated that ANKDD1B rs904743 was a significant risk factor for migraine susceptibility in China. Additionally, subgroup analysis by the Boruta algorithm showed a significant association between this SNP and migraine comorbid depression. Migraineurs with depression have been observed to have worse scores on the Beck Anxiety Inventory (BAI) and the Migraine Disability Assessment Scale (MIDAS). Conclusion The study indicates that there is an association between ANKDD1B rs904743 and susceptibility to migraine with and without depression in Chinese patients.